Identifying evidence of effectiveness in the co-creation of research: a systematic review and meta-analysis of the international healthcare literature. (11th October 2019) - Halvorsrud, Kristoffer; Kucharska, Justyna; Adlington, Katherine; Rüdell, Katja; Brown Hajdukova, Eva; Nazroo, James; Haarmans, Maria; Rhodes, James; Bhui, Kamaldeep
Abstract: Background: To investigate and address the evidence gap on the effectiveness of co-creation/production in international health research. Methods: An initial systematic search of previous reviews published by 22 July 2017 in Medline, Embase, PsycINFO, Scopus and Web of Science. We extracted reported aims, elements and outcomes of co-creation/production from 50 reviews; however, reviews rarely tested effectiveness against intended outcomes. We therefore checked the reference lists in 13 included systematic reviews that cited quantitative studies involving the public/patients in the design and/or implementation of research projects to conduct meta-analyses on their effectiveness using standardized mean difference (SMD). Results: Twenty-six primary studies were included, showing moderate positive effects for community functions (SMD = 0.56, 95%CI = 0.29–0.84, n  = 11) and small positive effects for physical health (SMD = 0.25, 95%CI = 0.07–0.42, n  = 9), health-promoting behaviour (SMD = 0.14, 95%CI = 0.03–0.26, n  = 11), self-efficacy (SMD = 0.34, 95%CI = 0.01–0.67, n  = 3) and health service access/receipt (SMD = 0.36, 95%CI = 0.21–0.52, n  = 12). Non-academic stakeholders that co-created more than one research stage showed significantly favourable mental health outcomes. However, co-creation was rarely extended to later stages (evaluation/dissemination), with few studies specifically with ethnic minority groups. Conclusions: The co-creation of research may improve several health-related outcomes and public health more broadly, but research is lacking on its longer term effects.